2013
DOI: 10.1002/wmh3.55
|View full text |Cite
|
Sign up to set email alerts
|

Comparing PACE with a Medicaid‐Only Managed Long‐Term Care Plan: Health Outcomes Over Time

Abstract: Outcomes from a partially integrated model of managed long‐term care—The VNS CHOICE program (VCP)—were compared to those from a fully capitated model—the Program of All‐Inclusive Care for the Elderly (PACE). A retrospective cohort design examined discharge, morbidity, and functional status for 3,200 individuals over 18 months. Although the two populations were close in average functional status, the PACE sample was sicker and more cognitively impaired. Higher rates of death were found in the PACE program (22 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 21 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…After excluding duplicates, 402 records were screened, from which 380 were excluded since the titles and/or abstracts were unrelated to the study objective or were not conducted in the US. Therefore, 22 records were reviewed in full, of which six met the eligibility criteria and were included in this scoping review [ 6 , 12 , 13 , 14 , 15 , 16 ]. The majority of the articles that were excluded did not compare the health outcomes of PACE participants with participants in other caregiving programs for older adults ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After excluding duplicates, 402 records were screened, from which 380 were excluded since the titles and/or abstracts were unrelated to the study objective or were not conducted in the US. Therefore, 22 records were reviewed in full, of which six met the eligibility criteria and were included in this scoping review [ 6 , 12 , 13 , 14 , 15 , 16 ]. The majority of the articles that were excluded did not compare the health outcomes of PACE participants with participants in other caregiving programs for older adults ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These three studies reported mixed results for PACE participants relative to their respective comparators. For instance, Nadash (2013) [13] reported a significant improvement in the IADL and ADL limitations in PACE participants compared to VCP participants, and Nadash (2004) [12] reported significantly fewer ADL and IADL limitations in PACE participants compared to MMLTC participants, suggesting that PACE is superior to VCP and MMLTC for managing functional disability among older adults. However, Kane et al (2002) [14] reported a significant proportion of PACE participants needed help with various measures of ADL and IADL limitations compared to WPP participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations